2012
DOI: 10.1123/ijsnem.22.5.353
|View full text |Cite
|
Sign up to set email alerts
|

Runners Greatly Underestimate Sweat Losses Before and After a 1-hr Summer Run

Abstract: The purpose of this study was to determine how accurately runners estimate their sweat losses. Male (n = 19) and female (n = 20) runners (41 ± 10 yr, VO2max 57 ± 9 ml · kg(-1) · min(-1) from the southeastern U.S. completed an ~1-hr run during late summer on a challenging outdoor road course (wet bulb globe temperature 24.1 ± 1.5 °C). Runs began at ~6:45 a.m. or p.m. Before and after running, participants filled race-aid-station paper cups with a volume of fluid they felt would be equivalent to their sweat loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
1
27
3
Order By: Relevance
“…In this study (O'Neal et al. ), the percentage of sweat loss trapped in the runner's clothing was higher (26% for men and 22% for women) than that of Cheuvront et al. () or this study, perhaps due in part to the higher relative humidity (mean of 86 and 72% during morning and evening runs), which could have limited the rate of sweat evaporation.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…In this study (O'Neal et al. ), the percentage of sweat loss trapped in the runner's clothing was higher (26% for men and 22% for women) than that of Cheuvront et al. () or this study, perhaps due in part to the higher relative humidity (mean of 86 and 72% during morning and evening runs), which could have limited the rate of sweat evaporation.…”
Section: Discussioncontrasting
confidence: 54%
“…; Noonan and Stachenfeld ; O'Neal et al. ) have shown that trapped sweat in clothing can lead to underestimations in sweat loss; however, this study is the first to measure trapped sweat in basketball uniforms and demonstrate that the magnitude of trapped sweat and the associated errors in sweat loss estimates are dependent upon common exercise/sport factors (exercise intensity, exercise duration, and sweat loss).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations